Farmer cooperatives and the changing agri-food system in China - Yang, H.; Vernooy, Ronnie; Leeuwis, Cees (SAGE Publications, 2018)
Consumer concerns are leading to changes in China’s food markets and demands for higher quality food. In this article, we explore the role of farmer cooperatives in China in linking farmers with high-quality food markets. We consider food quality a social construct and farmer cooperatives key players in the ‘quality battlefield’. Using a case study approach, we investigate the everyday practices of three farmer cooperatives. We show that farmer cooperatives are capable of establishing or joining quality food networks, but the benefits are often limited because of their weak position or instability of the network. Building strong alliances with other network actors is difficult because of cooperatives’ limited communication capacity and lack of economic and social capital. Our findings suggest that policies that support farmer cooperative capacity building at the micro level could improve the performance of smallholder farmers and their cooperatives in the expanding domestic quality food market.